(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Traditional Cultural Expressions form part of the whole corpus of Traditional Knowledge. They take different forms and can be tangible as well as intangible. Folklores are kind of Traditional Cultural Expressions that, mainly, includes intangible form of intellectual expressions of songs, music, theatre, lyrics, stories, by indigenous or tribal groups. Such, intangible intellectual expressions, like other forms of property, plays an important role in the lives of indigenous or tribal people. They are the significant source of recognition, identification and income generation. Unfortunately, the value of these intellectual expressions is ignored not only by the modern society but even by the present legal system operating in India. Traditional cultural expression, in their intangible form, find no place under the current regime of Intellectual Property Rights in India and are, thus, exposed to unwarranted commercial exploitation by the modern industries, with no flow of financial gains to them. This is because, the existing IPR regime consists of provisions relating to the protection and recognition of rights of identifiable creatorinventor for a limited period in their intellectual creations. There are many other legal and operation issues operating as hinderance in the process of granting equal protection to TCEs as IPRs under the current legal regime in India. Considering, their importance and role in the growth and development of the society, in the world of technology, it becomes an imperative step to entitle indigenous or tribal groups with equal legal rights as other inventors are hailed with under intellectual property laws in India. This requires enactment of an Act or a model law, that may be called “Model Law on the protection of India’s Traditional Knowledge” dealing, exclusively, with the redressal of problems faced by indigenous and tribal groups in the protection of their intangible traditional cultural expressions.